5-Fluorouracil-induced hyperammonaemic encephalopathy: A French national survey. (April 2020) - Boilève, Alice; Thomas, Laure; Lillo-Le Louët, Agnès; Gaboriau, Louise; Chouchana, Laurent; Ducreux, Michel; Malka, David; Boige, Valérie; Hollebecque, Antoine; Hillaire-Buys, Dominique; Jozwiak, Mathieu
Abstract: Background: 5-Fluorouracil (5-FU)-induced hyperammonaemic encephalopathy is a rare but serious 5-FU adverse drug reaction (ADR). Given the growing number of cancers treated with 5-FU and the paucity of data regarding this ADR, we performed a retrospective national survey to better characterise 5-FU-induced hyperammonaemic encephalopathy. Patients and methods: Since inception of the French pharmacovigilance database, we identified all patients who experienced 5-FU-induced hyperammonaemic encephalopathy. Variables regarding demographics, characteristics, management and outcome of patients were collected. Results: From 1986 to 2018, 30 patients were included. 5-FU-induced hyperammonaemic encephalopathy started 2 [1–4] days after 5-FU infusion onset. Most common neurological disorders were consciousness impairment, seizures and confusion. hyperammonaemia tended to be higher in patients with the lowest Glasgow score and admitted in intensive care unit (ICU) compared to non-ICU patients (250 [133–522] versus 139 [68–220] μmol/L respectively, p = NS). Dihydropyrimidine dehydrogenase deficiency was found in 27% of tested patients ( n = 3/11). Encephalopathy-induced mortality was 17%, 57% of patients were admitted in ICU and 70% had a complete neurological recovery within 5 [2–10] days. A 5-FU rechallenge was considered in 14 (67%) patients with neurological recovery and a relapse was observed in 57% of them. No 5-FU-induced hyperammonaemic encephalopathy relapse was observed as long as 5-FU rechallenge was performed with decreased 5-FU dosage. Conclusion: We report the largest cohort of 5-FU-induced hyperammonaemic encephalopathy cases so far. This ADR should be suspected and ammonaemia measured in all patients experiencing neurological disorders after 5-FU administration. In patients with complete neurological recovery, a 5-FU rechallenge could be cautiously considered. Highlights: Hyperammonaemic encephalopathy is a rare but serious adverse drug reaction of 5-FU. It should be evoked in all patients with neurological disorders after 5-FU infusion. Hyperammonaemia may result from Krebs cycle inhibition and/or urea cycle deficiency. A complete neurological recovery is expected in properly managed patients. A 5-FU rechallenge can be carefully considered in patients with neurological recovery.